CROSS-SECTIONAL POPULATION STUDIES: PREVALENCE OF METABOLIC SYNDROME AND ASSOCIATED RISK FACTORS AMONG MEN IN INDONESIA (Proceedings of the International Conference on Public Health, 2025)
: The prevalence of metabolic syndrome (MetS) is rapidly increasing globally.  An individual with MetS faces a fivefold increased risk of developing Type II diabetes (T2DM).  Indonesia is positioned fifth among the ten countries with the highest prevalence of diabetes patients globally.  Diabetes mellitus is a chronic illness that ranks third in mortality in Indonesia.  Men with prediabetes have a greater susceptibility to developing T2DM attributable to diminished insulin sensitivity compared to women.  This research aimed to ascertain the prevalence and risk factors of MetS among males in Indonesia.  The study employed a cross-sectional design involving 9,220 men aged 15 to 97 years, sourced from RISKESDAS 2018. MetS is defined based on 3 criteria (JIS, NCEP/ATPIII, IDF).   The risk factors for MetS include body mass index, smoking index, physical activity, alcohol use, intake of unhealthy foods, and consumption of fruits and vegetables.  Data analysis with the Chi-square test and multiple logistic regression. The highest prevalence of MetS was recorded using JIS criteria at 19.5%, followed by NCEP/ATP III and IDF criteria at 10.7% and 11.0%, respectively.  The prevalence of MetS and its components rises with advancing age. Factors associated with MetS were ages 30-79 years, overweight status, Grade 1 obesity, Grade 2 obesity, Grade 3 obesity, a smoking index of 200-400, a smoking index > 400, moderate physical activity, and poor physical activity.  Temuan penelitian ini akan membantu merancang program pencegahan untuk mengendalikan peningkatan prevalensi MetS pada pria di Indonesia.
Keywords: Sindrom metabolik; Indonesia; cross-sectional study; public health